Koszty jakości usług medycznych - Orliński, Ryszard (Quality Costs of Medical Service, 2005)
The quality of medical service equals to the satisfaction of a patient, an employee, also a payer and a health unit founder. Assuring the execution of medical service requires costs which are perceived according to the type of activity. However, the quality of service requires the understanding of quality costs which include conformity costs, non-conformity costs, and opportunity costs. Skilful management of quality costs enables wide-ranging of medical services, which results in effective managing a health care unit, which is of vital importance, especially taking the current situation in health service into consideration.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 260-270